2021
DOI: 10.1111/petr.14015
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation in patients with childhood cerebral adrenoleukodystrophy: A single‐center experience “Better prognosis in earlier stage”

Abstract: Background: ALD is a rare X-linked peroxisomal metabolic disorder with many distinct phenotypes of disease that emerge on a wide scale from adrenal insufficiency to fatal cALD which progresses to a vegetative state within a few years. Currently, HSCT is the only treatment method known to stabilize disease progression in patients with cALD. In this study, we aim to report our HSCT experience in patients with cALD and the factors that determine the success of HSCT, as a single-center experience. Methods:The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As previously reported, treatment by HSCT leads to statistically greater rates of survival and rates of survival free of major functional disabilities among those with early disease as compared to those with advanced disease (Kühl et al, 2018; Yalcin et al, 2021), highlighting the critical importance of early diagnosis. In the United Kingdom and elsewhere, an initial diagnosis of ALD within a family will lead to a programme of extended family testing to identify others at risk of disease (Bezman et al, 2001).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As previously reported, treatment by HSCT leads to statistically greater rates of survival and rates of survival free of major functional disabilities among those with early disease as compared to those with advanced disease (Kühl et al, 2018; Yalcin et al, 2021), highlighting the critical importance of early diagnosis. In the United Kingdom and elsewhere, an initial diagnosis of ALD within a family will lead to a programme of extended family testing to identify others at risk of disease (Bezman et al, 2001).…”
Section: Discussionmentioning
confidence: 69%
“…A scoring system (the Loes score) is used to make decisions about whether to proceed to transplant. Several multinational prospective studies have assessed treatment outcomes of children receiving HSCT and consistently reported statistically greater rates of survival and rates of survival free of major functional disabilities among those with early disease as compared to those with advanced disease (Kühl et al, 2018; Yalcin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is no approved treatment for ALD. In early cases of CALD, allogenic hematopoietic stem cell transplantation (HSCT) is recommended to prevent disease progression and long-term stabilization (26,27). Although the direct mechanism of HSCT activity is not clear, it is assumed that transplanted HSCs deliver the cellular source of the intact ABCD1 gene and corrected VLCFA ratio (12).…”
Section: Discussionmentioning
confidence: 99%
“…HCT has been effective in treating CCALD since the early 1990 s and is presently the standard of care 44,45 . Successful treatment typically halts the long‐term advancement of cerebral demyelination, although it is common to observe some degree of clinical progression in the months following HCT as disease stabilizes 11,32,46,47 . In terms of neurocognitive outcomes, studies have consistently demonstrated that HCT performed early in the disease process results in better preservation of abilities.…”
Section: Males With Aldmentioning
confidence: 99%
“…44,45 Successful treatment typically halts the long-term advancement of cerebral demyelination, although it is common to observe some degree of clinical progression in the months following HCT as disease stabilizes. 11,32,46,47 In terms of neurocognitive outcomes, studies have consistently demonstrated that HCT performed early in the disease process results in better preservation of abilities. Shapiro and colleagues were the first to report long-term neurocognitive outcomes after HCT among a set of 8 boys with CCALD treated before disease was advanced.…”
Section: Neuropsychological Outcomes After Allogeneic Hct For Ccaldmentioning
confidence: 99%